Study protocol: a randomised controlled trial investigating the effect of a healthy lifestyle intervention for people with severe mental disorders - Baker, Amanda (BioMed Central, 2011)
BACKGROUND: The largest single cause of death among people with severe mental disorders is cardiovascular disease (CVD). The majority of people with schizophrenia and bipolar disorder smoke and many are also overweight, considerably increasing their risk of CVD. Treatment for smoking and other health risk behaviours is often not prioritized among people with severe mental disorders. This protocol describes a study in which we will assess the effectiveness of a healthy lifestyle intervention on smoking and CVD risk and associated health behaviours among people with severe mental disorders. METHODS/DESIGN: 250 smokers with a severe mental disorder will be recruited. After completion of a baseline assessment and an initial face-to-face intervention session, participants will be randomly assigned to either a multi-component intervention for smoking cessation and CVD risk reduction or a telephone-based minimal intervention focusing on smoking cessation. Randomisation will be stratified by site (Newcastle, Sydney, Melbourne, Australia), Body Mass Index (BMI) category (normal, overweight, obese) and type of antipsychotic medication (typical, atypical). Participants will receive 8 weekly, 3 fortnightly and 6 monthly sessions delivered face to face (typically 1 hour) or by telephone (typically 10 minutes). Assessments will be conducted by research staff blind to treatment allocation at baseline, 15 weeks, and 12-, 18-, 24-, 30- and 36-months. DISCUSSION: This study will provide comprehensive data on the effect of a healthy lifestyle intervention on smoking and CVD risk among people with severe mental disorders. If shown to be effective, this intervention can be disseminated to treating clinicians using the treatment manuals. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry (ANZCTR) identifier: ACTRN12609001039279